Democracy against itself : sustaining an unsustainable idea - Chou, Mark (Political scientist) (Edinburgh University Press, 2014)
By their very nature, all democracies have the potential to destroy themselves. But this fact is too rarely documented by acolytles of the system. In the decades since Joseph Goebbels, then Reich Minister of Propaganda, reminded the world that it 'will always remain one of the best jokes of democracy, that it gave its deadly enemies the means by which it was destroyed', democrats have quickly forgotten just how precarious a political framework it can be. Using the collapse of democracy in ancient Athens and the Weimar Republic, as well as the uncertain fate of democratic rule in the United States and China today as illustrative examples, Mark Chou examines the conditions and characteristics of democracy that make it prone to self-destruct. In drawing out the political lessons from these past collapses, he explains how a democracy can, simply by being democratic, sow the seeds of its own destruction. Explores why democracies fail, both theoretically and empirically 4 case studies: democratic Athens, the Weimar Republic, contemporary American democracy and China's fledging efforts to democratise Takes political lessons from the case studies to highlight the predicaments faced by weak and failing democracies today